(untitled) (Journal of Creative Industry and Sustainable Culture, 2022)
Exciting movies are films with components that can affect a person’s psychology and emotions including towards children. The Harry Potter movie is basically a show aimed at children after being adapted from a novel. It is about a world that full of magic and beautiful personalities that even adults are amazed by the links made between the minute details within every scene. However, there are several different opinions related to the story that say that the story has either a negative or positive effect on the children. This research was done to analyse the relationship between element of concrete operational concept and the impactful scene from one of Harry Potter movie, which is Harry Potter and the Sorcerer’s Stone(2001). This research uses qualitative approach to answer all the research objectives with applying the method of descriptive analysis and focus on the materials collection based on phenomenally recorded news and feed backs from public as well as the support with authors, newspapers, journal, and other sources. Also, the cognitive operational concept by Jean Piaget’s cognitive development theory is use in this research to draw the conclusion at the end of the study. Thus, Harry Potter and the Sorcerer’s Stone (2001) can be watched by the children especially children under the age of 7 until 11 years old after analyzing through each scene and relate it with the theory mentioned above.